The price of humanity : how philanthropy went wrong and how to fix it - Schiller, Amy (Melville House, 2023)
A journalist, academic and consultant evaluates the history of philanthropy, from the ideas of St. Augustine to the work of Lebron James, arguing that philanthropy can no longer be premised around basic survival and that public institutions must assume that burden so that philanthropy can support human flourishing as originally intended.